Time-barring and prescription of pension funds : a legal perspective - Matloga, Nicholas Sylva (My University, 2012)
The amendment of section 30I (3) of the Pension Funds Act No.24 of 1956 by the provisions of section 30I of the Pension Funds Amendment Act No.11 of 2007 poses a serious threat to the constitutional right to social security (Section 27 (1) (c) of the Constitution). The amendment places this challenge on this right because it places some form of time-barring on the member of the fund or the complainant (his or her dependent) when lodging a pension funds complaint after a prescribed time has elapsed (three years) and the Adjudicator will no longer have no powers to condone such a late referral despite good cause shown and prospects of success on the part of the complainant. The said amendment has placed the poor more especially those in the rural areas in a disadvantageous position, because most of them are illiterate and not aware of their pension law rights. This means that even though they are entitled to the pension funds benefits, they cannot access it if they lodged their complaint outside the three-year period.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2012
Keywords: Pension funds; Social security; Social insurance; Insurance -- Social aspects; Pension trusts; Social security -- Law and legislation -- South Africa